Phase-shifting image-plane digital holography with elliptical vortex sieve. (July 2019) - Zhang, Xiuping; Zhang, Junyong; Zhang, Yanli; Liu, Dean; Zhu, Jianqiang
Highlights: An effective scheme for phase-shifting image-plane digital holography with elliptical vortex reference beam is proposed. An amplitude-only elliptical vortex sieve as a new kind of phase shifter. The elliptical vortex sieve is convenient and widely applied in phase-shifting digital holography. Abstract: Phase-shifting image-plane digital holography is considered as a widely-used measuring method for observation of micro-scale phase objects and for nondestructive testing of phase morphology. The elliptical vortex sieve is a kind of amplitude-only diffractive lenses which can be used for focusing and imaging from coherent X-rays to terahertz regime. Here an elliptical vortex lens is introduced into phase-shifting image-plane digital holography, and verifies the validity of phase shift by measuring a test target and the multiplanar focal spots of a Taiji lens. The experimental results agree well with the theoretical analysis. Owing to amplitude-only diffractive lenses, they will have great potential in X-rays holography and biochemical microscopy for the next generation of synchrotron radiation and free electron laser in the future.